Defensive function of persecutory delusion and discrepancy between explicit and implicit self-esteem in schizophrenia: study using the Brief Implicit Association Test - Nakamura M (Dove Medical Press, 2014)
Mitsuo Nakamura,1 Tomomi Hayakawa,2 Aiko Okamura,3 Mutsumi Kohigashi,4 Kenji Fukui,1 Jin Narumoto1 1Department of Psychiatry, Graduate School of Medicine, Kyoto Prefectural University of Medicine, Kyoto, Japan; 2Gojouyama Hospital, Nara, Japan; 3Yashio Hospital, Saitama, Japan; 4Department of Psychiatry, Kyoto Second Red Cross Hospital, Kyoto, Japan Background: If delusions serve as a defense mechanism in schizophrenia patients with paranoia, then they should show normal or high explicit self-esteem and low implicit self-esteem. However, the results of previous studies are inconsistent. One possible explanation for this inconsistency is that there are two types of paranoia, “bad me” (self-blaming) paranoia and “poor me” (non-self-blaming) paranoia. We thus examined implicit and explicit self-esteem and self-blaming tendency in patients with schizophrenia and schizoaffective disorder. We hypothesized that patients with paranoia would show lower implicit self-esteem and only those with non-self-blaming paranoia would experience a discrepancy between explicit and implicit self-esteem. Methods: Participants consisted of patients with schizophrenia and schizoaffective disorder recruited from a day hospital (N=71). Participants were assessed for psychotic symptoms, using the Brief Psychiatric Rating Scale (BPRS), and self-blaming tendency, using the brief COPE. We also assessed explicit self-esteem, using the Rosenberg Self-Esteem Scale (RSES), implicit self-esteem, using Brief Implicit Association Test (BIAT), and discrepancy between explicit and implicit self-esteem. Results: Contrary to our hypothesis, implicit self-esteem in paranoia and nonparanoia showed no statistical difference. As expected, only patients with non-self-blaming paranoia experienced a discrepancy between explicit and implicit self-esteem; other groups showed no such discrepancy. Conclusion: These results suggest that persecutory delusion plays a defensive role in non-self-blaming paranoia. Keyword: coping style, poor me paranoia, remitted paranoid delusion, external attribution